Physical and emotional violence against women during pregnancy in Zambia - Mwaba, SOC; Menon, JA; Kusanthan, T. (IJRDO - Journal of Social Science and Humanities Research, 2017)
This study used data from the 2013 Zambia Demographic Health Survey (ZDHS) based on a nationally representative sample carried out by Central Statistical Office of Zambia. This paper analyzed a special module designed to collect information on the extent to which women experience physical, emotional and sexual violence in Zambia. The analysis of this paper is based on 1,420 pregnant women aged between 15 and 49 years. It was found that 31% of the pregnant women had experienced physical violence from their partners whereas 17% of the pregnant women had experienced emotional violence from their partners in their relationships. Regression analysis further showed that age, number of children, exposure to media and alcohol consumption by the partner were all related to both physical and emotional Intimate Partner Violence (IPV). It is recommended that the government in Zambia and other organizations involved in curbing Gender Based Violence (GBV) and in particular IPV should also focus on pregnant women and re-double their efforts in the fight. It is also recommended that a cultural mental shift was required by both men and women in order to effectively fight the scourge of IPV.